Educational Inequality and Its Impact on Social and Economic Opportunities in Rural India - Kumar, Arjun; Sharma, Priya; Patel, Ravi; Gupta, Ananya; Singh, Vikram (International Journal of Humanities, Management and Social Science (IJ-HuMaSS), 2024)
Educational inequality remains a significant challenge in rural India, with disparities in access to infrastructure, teacher quality, and technology hindering equitable learning opportunities. This study examines these inequalities in two rural regions: Barwani, Madhya Pradesh, and Kalahandi, Odisha. Using a mixed-methods approach, the research combines qualitative interviews with students, teachers, and policymakers, alongside quantitative data on enrollment, infrastructure, and learning outcomes. Findings reveal that 72% of schools in Barwani lack science laboratories, while 65% of schools in Kalahandi lack digital tools, reflecting severe infrastructural gaps. High student-to-teacher ratios of 70:1 in Barwani and 60:1 in Kalahandi further strain educational quality, exacerbated by a lack of trained teachers. Poor access to technology and unreliable internet connectivity limit digital literacy, perpetuating the digital divide. The study also evaluates government interventions such as the Sarva Shiksha Abhiyan and digital education initiatives, finding implementation inconsistencies in remote areas. The findings highlight how educational inequality restricts social mobility and economic opportunities, particularly in underdeveloped regions. Future research should focus on the effectiveness of targeted policies and explore innovative, technology-driven solutions to bridge these disparities, fostering equitable educational development and sustainable growth in rural India.